Membership and Feedback on the American Academy of Orthopaedic Surgeons and Other Subspecialty Societies: A Survey Study of Orthopaedic Surgeons. (3rd November 2022) - Saxena, Arjun; Toci, Gregory R.; Brush, Parker L.; Reinhardt, Alexis; Beredjiklian, Pedro K.; Hilibrand, Alan S.; Vaccaro, Alexander R.; Fletcher, Daniel
Abstract : Introduction: Orthopaedic surgeons face decreased reimbursement, lower income, and increased rates of burnout. As subspecializing through fellowship training in orthopaedics becomes more and more prevalent, the value of membership to a general orthopaedic society (American Academy of Orthopaedic Surgeons [AAOS]) warrants investigation. Methods: One hundred thirty orthopaedic surgeons were surveyed by e-mail through a 14-item anonymous survey administered through SurveyMonkey. The survey inquired about surgeon experience, practice type, fellowship training, and details regarding AAOS and subspecialty society membership. Results: The response rate was 67%, with 94% of respondents indicating that they were members of AAOS and a subspecialty society. The most common reasons for AAOS membership were tradition (65, 74.7%), continuing medical education (46, 52.9%), maintenance of board certification (44, 50.6%), and political advocacy (40, 46.0%). The most common reasons for subspecialty society membership were continuing medical education (73, 83.9%), tradition (49, 59.8%), and political advocacy (33, 40.2%). Discussion: Most surgeons in our study cohort were members of both AAOS and a subspecialty society, but the reasons for membership in each differed. Almost 80% of respondents think their subspecialty society provides all their professional needs. The orthopaedic societies need to continue to evolve to provide value to their members to succeed in the future.